A Dual Band U‐Slot Printed Antenna Array for Lte and Wimax Applications. Issue 12 (23rd September 2013) - Ali, Muhsin; Khawaja, Bilal A.; Tarar, Munir A.; Mustaqim, Muhammed
ABSTRACT In this article, a dual‐band coaxial‐fed 2 × 2 rectangular U‐Slot microstrip patch antenna array for multiple input multiple output applications, in 4G long term evolution (LTE) and WiMAX systems, is presented. The targeted frequency bands are: (1) LTE Band‐1 at 2.1 GHz, and (2) WiMAX at 3.5 GHz. Simple design procedure and optimization techniques are discussed to achieve the desired parameters. Antenna design and simulation is performed in Agilent ADS Momentum using RT/Duroid substrate (εr = 2.2 and h = 3.175 mm). Substrate losses are also taken into account during design and simulation processes. The antenna is fabricated and characterized, and a comparison between the simulated and measured antenna is presented. The achieved impedance bandwidths/gains (determined by benchmark of voltage standing wave ratio ≤ 2) reach 2.4%/11.1 dBi and 2%/6.6 dBi for 2.1 and 3.5 GHz bands, respectively. The proposed antenna can be used as a template to form larger arrays. © 2013 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:2879–2883, 2013